Assessing attitudes and actions of pediatric dentists toward childhood obesity and sugar‐sweetened beverages. (15th July 2017) - Wright, Robin; Casamassimo, Paul S.
Abstract: Objectives: Childhood obesity is a major US health concern, and oral health professionals have opportunities to participate in an interprofessional effort to intervene owing to their access to young patients and their abilities in addressing obesity‐related dietary habits like consumption of sugar‐sweetened beverages (SSBs). This study determined attitudes, behaviors, future intentions, and perceived barriers of pediatric dentists regarding efforts to prevent childhood obesity and reduce children's consumption of SSBs. Methods: The American Academy of Pediatric Dentistry conducted an online electronic survey with a convenience sample of approximately 7, 450 pediatric dentists and pediatric dental residents during spring 2016. Results: Over 17 percent of pediatric dentists offer childhood obesity interventions. Of those not providing interventions, 67 percent were interested in offering obesity‐prevention services. Nearly 94 percent of pediatric dentists offer information or other interventions on consumption of SSBs. Statistically significant barriers to providing healthy weight interventions were fear of offending parents, appearing judgmental, or creating parent dissatisfaction and a lack of parental acceptance of guidance about weight management from a dentist. Significant barriers to SSB interventions were sufficient time and health professional education. Conclusions: More pediatric dentists stated they offer childhood obesity interventions than in previous surveys reporting 6 percent, but respondents suggested that a child's weight is seen as a medical rather than dental issue. Most pediatric dentists provide interventions related to consumption of SSBs, perceiving the issue as integral to their care of children.